ChemInform Abstract: Intramolecular Cyclization Manifolds of 4‐Alkylpyridines Bearing Ambiphilic Side Chains: Construction of Spirodihydropyridines or Benzylic Cyclization via Anhydrobase Intermediates. Issue 3 (22nd January 2013) - Parameswarappa, Sharavathi G.; Pigge, F. Christopher
Abstract Pyridines containing a β‐keto amide moiety can be converted into spirocyclic dihydropyridines or lactams depending on the substitution pattern and the conditions.